Prison Masculinities International Perspectives and Interpretations (Taylor & Francis, 2023)
This edited book explores prison masculinities, drawing from a wide range of international researchers to highlight how masculinities may divert from the ""hypermasculine"" or macho typology typically found in the prison masculinities literature. The book includes a diverse selection of writing on masculinities ""in"" and ""of"" prison; masculinities experienced by those living within, working, and experiencing prison as well as historical and critical accounts of masculinities from around the world. The contributors highlight how masculinities are experienced in a multitude of ways as is evidenced in both qualitative and quantitative research with men before, during, and after imprisonment; with correctional officers and staff; in the analysis of public records, in the critical examination of Sykes' seminal work; and in historical and contemporary Australian society. Evidenced in writing drawn from Australia, the Dominican Republic, Ukraine, Hong Kong, the United States, Scotland, and the Netherlands, the contributors acknowledge that rather than being fixed, discourses around prison masculinities now include sexuality, gender identity, and diverse understandings around masculinities as strategic, hegemonic, and ever changing. Prison Masculinities is important reading for students and scholars across disciplines, including criminology, sociology, gender studies, law, international relations, history, health, psychology, and education.
English
Keywords: Crime & criminology; Gender studies, gender groups; Gender studies: men; Penology & punishment; carceral, prison, colonialism, convict, inclusive, masculinity, misconduct, offender, piety, prisons, power, punishment, surviving, violent, vulnerability, violence, undoing